Public demand for eco-efficient concepts in urban development - Junnila, Seppo; Ristimäki, Miro (International Journal of Strategic Property Management, 2012)
Global warming has brought new challenges to urban development worldwide. Built environment and cities are estimated to cause some 40–70% of the environmental impacts. This questions our current urban development practises and challenges us to find new solutions to manage the issues. The purpose of this study is to identify feasible eco-efficient concepts that can be implemented in the urban development process. These concepts are identified with a constructive research method, where potential concepts are originally identified from literature and further enhanced with thematic expert interviews, and finally, the suggested concepts are tested with a questionnaire and presented in an integrated framework for the eco-efficient concepts to better understand the requirements and opportunities in public urban development. The results showed that the urban development concepts that were most appealing to public stake holders were; an integrated design process, eco-efficient traffic and transportation solutions, and eco-efficient complementary development. Local energy procurement and management was also perceived as relatively lucrative services when developing eco-efficient urban areas. This study provides an extensive information platform (different ideas, themes, and concepts) to promote eco-efficiency in urban development in order to maintain and improve the sustainable quality of life and welfare in our urban society.First Publish Online: 12 Apr 2012